Implementasi Pendidikan Holistik dalam Kurikulum Pendidikan Agama Islam - Tahtimatur Rizkiyah (Jurnal Hikmatuna, 2017)
Holistic education is effort to build all of student’s potentials to be whole person, who can realize their connection to God, human, and nature well. This research describe about curiculum of Quran hadith subject Madrasah Tsanawiyah in holistic education perspective. The aim of Quran hadith subject is implant divinity and humanity values wich must be applicated in daily life, and the students have capability of holistic thinking. The Graduation Competency Standard of Quran Hadith subject is the students have competency of knowledge, attitude, and values. The curriculum content of Quran Hadith subject include divinity, humanity, and nature insight. The type of research is library research that use qualitative methode. The primary theory approach is theory of holistic education, wich supported by another theories such as tafsir, filsafat, and phsicology. Tehnics of data processing in this research use documenter, descriptive analysis, and content analysis.